2004
DOI: 10.1210/jc.2003-031624
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin B and Anti-Müllerian Hormone, But Not Testosterone Levels, Are Normal in Infants with Nonmosaic Klinefelter Syndrome

Abstract: Klinefelter syndrome is a major cause of infertility in the male. Nevertheless, pregnancies were recently obtained by intracytoplasmic injection of sperm retrieved by surgery or ejaculation, underscoring the need to understand the role of Sertoli and Leydig cell secretions during development. In 18 infants with prenatally diagnosed homogenous 47,XXY karyotype, blood samples were taken from birth to 3 yr of age. Inhibin B (INHB), anti-Müllerian hormone (AMH), testosterone, FSH, and LH levels were compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
114
2
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 29 publications
11
114
2
7
Order By: Relevance
“…Thus, impaired T secretion is not an evident feature of KS boys during puberty. In fact, to our knowledge, only two studies on KS boys have demonstrated diminished T secretion before puberty (30,31), but these studies comprised infant KS boys, and the results cannot therefore be directly extrapolated to peripubertal and pubertal KS subjects.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, impaired T secretion is not an evident feature of KS boys during puberty. In fact, to our knowledge, only two studies on KS boys have demonstrated diminished T secretion before puberty (30,31), but these studies comprised infant KS boys, and the results cannot therefore be directly extrapolated to peripubertal and pubertal KS subjects.…”
Section: Discussionmentioning
confidence: 92%
“…The mini-puberty represents a window suitable for studying the function of the pituitary-gonadal axis at this young age by measuring the spontaneous, basal hormone levels (32). Although controversies exist as to whether the HPG axis is impaired in KS infants (16,33,34,35), the latest and largest study on the mini-puberty in KS demonstrated normal testosterone concentrations (35). Importantly, however, the testosterone concentrations were below the median of the controls, which may indicate a subtle Leydig cell dysfunction, although this was not supported by an elevation of LH concentrations (35).…”
Section: Testicular Endocrinologymentioning
confidence: 99%
“…Anti-Mullerian hormone (AMH) was measured with a solid phase sandwich assay (DSL-France, Cergy-Pontoise, France). Details of the assays used and their precision profiles have been described previously (6,7). Immunoreactive inhibin-a was measured by RIA using antiserum 1989 raised against purified 31 kDa bovine inhibin, kindly donated by D M de Kretzer (Monash University, Clayton, Australia) (8).…”
Section: Laboratory Assaysmentioning
confidence: 99%